Optimal Calculation Method of Mean Equivalent Diameter of Floc Particles Based on MCC - Jun Liu; Siqi Peng; Nan Zhou (Complexity)
In the process of water treatment, coagulation is an important process to remove minerals and organic particles from raw water, which has typical time delay and nonlinearity. The effect of coagulation directly affects the turbidity of the effluent. According to the good correlation between the mean equivalent diameter of floc particles and the turbidity of effluent water, the image processing method is used to preprocess the floc image, the parameters of floc particles are quantitatively analyzed, and the mean equivalent diameter of floc particles is obtained, which is used as one of the bases for the control of coagulant dosage. However, no matter whether the coagulation process in actual situations interferes with the outside world or not, the equivalent diameters of floc particles after coagulation may have abnormal and invalid values, which may lead to a problem that there is a large difference between the mean equivalent diameter of floc particles calculated by a least square method and the mean valid equivalent diameter of floc particles. In response to this problem, this article proposes an optimal calculation method of the mean equivalent diameter of floc particles based on the maximum correntropy criterion (MCC) to reduce the negative impact of the abnormal and invalid equivalent diameters of floc particles on the mean equivalent diameter and provide an important reference data for the precise dosing control of coagulants. Finally, the feasibility of the theoretical results is verified by several numerical experiments.